Experimental Analysis of Climate Parameters Effect on Structural Steel Atmospheric Corrosion Rate in Medan City Environment - Tanjung, Iqbal; Lubis, Riadini Wanty; Gultom, Zuli Agustina; Affandi, Affandi; Siregar, Chandra A; Fonna, Syarizal (SINTEK JURNAL: Jurnal Ilmiah Teknik Mesin, 2024)
This study aims to explore the important role of weather parameters i.e. humidity, rainfall, temperature, and wind speed on the corrosion rate in the Medan City atmospheric environment. Three forms of material with low carbon steel type were prepared in this investigation. The exploration process was conducted for six months starting from June to December 2023, in the open area of the Engineering Faculty, Universitas Muhammadiyah Sumatera Utara. Corrosion rate assessment is carried out monthly using the weight loss method and climate parameter data is obtained from the Medan City Meteorology and Geophysics Agency (BMKG). The dimensions, initial preparation, data collection, post-test material preparation, and corrosion rate calculations refer to the ASTM G1 and G50 standards. Regression analysis and Pearson correlation explain the relationship between corrosion rate and climate parameters. The investigation showed that the corrosion rate fluctuated monthly from 0.1 to 0.5 mpy. By referring to corrosion resistance data on metal materials, it was found that the corrosion level was in the good resistance category "outstanding". Based on the regression analysis results, humidity, local temperature, and rainfall play an important role in the atmospheric corrosion rate in Medan City. The percentage of closeness between variables is ± 98% and the standard deviation is ± 0.0001. Further development is needed to determine other parameters that also play an important role in atmospheric corrosion rate and forming a random forest model for predicting future corrosion rates.